Asymptotic decay of velocity of whipping jet in electrospinning. (5th March 2021) - Lei, Sailing; Quan, Zhenzhen; Qin, Xiaohong; Yu, Jianyong
Abstract: In electrospinning, the whipping jet plays a significant role in determining the microstructure of electrospun nanofibers. So far, however, it is extremely challenging to control the behavior of whipping jet precisely owing to its small diameter and rapid motion. In the present work, dynamic models are established to predict the velocity of whipping jet, where the velocity is tuned by surface charge. It is found that the variation of velocity of whipping jet with motion time follows a scaling law with an exponent of −1/3. Moreover, the relationship between velocity of whipping jet and axial distance obeys a scaling law with an exponent of −1/2. In addition, the theoretical predictions show a good agreement with the experimental results. This work provides a new strategy for the accurate control of velocity and stretching of whipping jet, promoting the morphological and structural design of electrospun nanofibers. Graphical abstract: Image 1 Highlights: The spatial- and temporal-models of velocity of whipping jet have been established. The velocity is proportional to −1/3 power of motion time in electrospinning. The velocity decays as a power law with exponent −1/2 along the axial distance. The proposed model can predict and control the jet stretching.